IMPLEMENTATION OF BLUE OCEAN STRATEGY (BOS) AT PT. ANEKA DIGITAL SUKSESINDO IN THE EFFORT TO INCREASE THE COMPETITIVE ADVANTAGE AGAINST THE COMPETITORS - Andi Suhendi, Acep (Dinasti International Journal of Economics, Finance & Accounting, 2020)
The increasing competition in the business world requires a company to always make transformation not only to meet the company's targets but also for business sustainability or survival. The similar thing happened with PT.Aneka Digital Suksesindo which is one of the PMA (Foreign Investment Company) from China which is engaged in the distribution of electronic products made in China which is always innovating in order to maintain its existence in Indonesia. Some of its superior products are 1. Black Shark which is mobile gaming that offers maximum performance. It is a smart phone which is able to hold on for hours to play games and fast charging, 2. Amazfit Smartwatch is a smart watch from Xiaomi that can be used to monitor heart rate, real GPS time to record running track, speed and distance. This study aims to explain the implementation of the Blue Ocean Strategy in an effort to improve competitive advantage and also to determine the conditions of the internal and external environment through SWOT Analysis, namely Strength, Weakness, Opportunity, Threat (Threat) at PT. Aneka Digital Suksesindo. Based on the type of research that is descriptive research using a qualitative approach